Recognizing Volunteers: Considerations for Volunteer Organizations and Coordinators - Tyler Carney; Deanna Brock; Kiera Packer; Vivian Rodriguez; Matthew Benge (EDIS, 2025)
Volunteers represent a critical population who contribute to nonprofits’ capacity to achieve missions and goals. Volunteers hold various motivations that enable them to pursue their important work. Volunteer coordinators and managers can implement appropriate recognition strategies to meet the motivational needs of their organization’s volunteers. This publication looks at volunteer motivations and relevant recognition strategies. Written by Tyler Carney, Deanna Brock, Kiera Packer, Vivian Rodriguez, and Matt Benge, and published by the UF/IFAS Department of Agricultural Education and Communication, May 2025.